Changes in 24-hour movement behaviours during the transition from primary to secondary school among Australian children. Issue 8 (3rd August 2022) - Chong, Kar Hau; Parrish, Anne-Maree; Cliff, Dylan P.; Dumuid, Dorothea; Okely, Anthony D.
ABSTRACT: This study examined concurrent changes in all components of 24-h movement behaviours (24-h MB) (sleep, sedentary behaviour [SB] and physical activity [PA]) and compliance with the Australian 24-Hour Movement Guidelines over the primary to the secondary school transition period. The analytical sample included 83 children (60.2% girls) who provided valid accelerometer-measured 24-h MB data during their final year of primary school (T1) and first year of secondary school (T2). Self-reported participation in domain-specific SB and PA, socio-demographic characteristics and weight status were also assessed. Change in 24-h MB composition from T1 to T2 was analysed using a compositional multivariate linear model for repeated measures. The difference in the proportion of meeting the 24-hour integrated movement guidelines was assessed using a McNemar–Bowker test. An unfavourable change was observed in the 24-h MB composition ( p  < .0001), with increased time spent in SB (+58 min/day) and decreased time in sleep (−13 min/day), Iight-intensity PA (−13 min/day) and moderate- to vigorous-intensity PA (−14 min/day). Domain-specific SB results indicated an increase in recreational screen time (+45 min/day) and out-of-school educational activities (+25 min/day). No significant changes were observed for domain-specific PA. The proportion of children meeting the 24-hour integrated movement guidelines also declined (20.5% vs. 3.6%; p  < .0001). Change in 24-h MB was larger on weekdays than weekends ( p  < .0001); but this was not moderated by socio-demographic characteristics or weight status. These findings suggest that an integrated intervention approach targeting weekdays may be beneficial to promote adherence to healthy 24-h MB during the primary to the secondary school transition period. Highlights This study investigated how the 24-hour movement behaviour composition (i.e., time spent in sleep, sedentary behaviour and physical activity) changes and its impact on children's compliance with the 24-hour integrated movement guidelines during the primary to secondary school transition period. There was an unfavourable change in the accelerometer-measured 24-hour movement behaviour composition, with increased time spent in sedentary behaviour and decreased time in sleep, light-intensity physical activity and moderate- to vigorous-intensity physical activity. The change in weekday composition was significantly more prominent than change on weekends. The observed increase in sedentary behaviour may be attributed in part to an increase in recreational screen time and out-of-school educational activities in secondary schools. These behavioural changes were reflected in decreased compliance rates with the individual and integrated 24-hour movement guidelines, with the largest decline observed in the sleep guideline. Our findings highlight the need for an integrated intervention approach to support children to develop and/or maintain healthy movement behaviour habits throughout the school transition period.